ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 56/PUU-XX/2022 TENTANG PENGUJIAN MATERIIL PASAL 27 A AYAT (2) HURUF B UNDANG-UNDANG NOMOR 7 TAHUN 2020 TENTANG MAHKAMAH KONSTITUSI - Samuel Yakub Radja Gnting Suka; Mexsasai Indra; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Judicial power is an independent and independent power that carriesout a judicial function in the field of justice. The Constitutional Court is a stateinstitution that carries out the functions of judicial power which is grantedconstitutional authority in Article 24 letter C of the 1945 Constitution of theRepublic of Indonesia. In addition, the Judicial Commision is part of the judicialpower but does not carry out a judicial function. Judicial Commision is only aninstitution that balances the power of the judiciary which has the authority by theConstitution to maintain and uphold the nobility and behavior of judges.The type of research used by the author is normative legal research orwhat is known as "legal research". Which means that this legal research, law isoften conceptualized as what is written in statutory regulations (law in book) orlaw. Regarding the Constitutional Court Decision Number 56/PUU-XX/2022which conducted a material review of Article 27 A paragraph (2) Letter B LawNumber 7 of 2020 Concerning the Constitutional Court.The Constitutional Court Decision Number 56/PUU-XX/2022 states that1 (one) member of the Judicial Commission as one of the elements in theHonorary Council of the Constitutional Court is contrary to the Constitution anddeleted. Meanwhile, the background or urgency for the establishment of theJudicial Commision was to overcome judicial mafia practices that hadmushroomed at that time in Indonesian courts, as well as to restore publicconfidence in the judiciary. Judicial Commision is mandated by Article 24Bparagraph (2) to protect and uphold the honor of judges, while the ConstitutionalCourt is of the opinion that the judges in question are different fromConstitutional Court judges in their positions. in the Constitution itself there is nodistinction between judges according to their position or function. It is feared thatthe Judicial Commision's exception will further open up opportunities for judicialmafia practices. In this regard, this decision will also result in a situation thatmakes the Court a super body judicial institution because there is no institutionoutside the Court that will supervise and uphold the ethics of the ConstitutionalKeywords: Decision MK, MKMK, KY Supervision